Thermo-mechanical characterization of Manicaria Saccifera natural fabric reinforced poly-lactic acid composite lamina. (February 2016) - Porras, A.; Maranon, A.; Ashcroft, I.A.
Abstract: The development and thermo-mechanical characterization of a novel green composite lamina, made of PolyLactic Acid (PLA) reinforced with a natural fabric extracted from Manicaria Saccifera palm, are presented. The composite was characterized by thermal-analysis (TGA), tensile, flexural, and izod impact tests, and scanning electronic microscopy (SEM). TGA analysis showed that the degradation process of the composite started earlier than that of neat PLA due to the lower thermal stability of the fabric. The mechanical tests showed that PLA properties were improved. The tensile strength, elastic modulus and impact resistance were improved by 26%, 51% and 56% respectively. Good dispersion and mechanical interlocking of PLA into the fabric were seen by SEM explaining the improvements of the mechanical properties of the composite. In summary, the good tensile properties and the excellent energy absorption capabilities of the MF/PLA composite lamina show great potential of Manicaria fabric as reinforcement in green composites.